Struggle for peace the 25 year journey of the ABSDF. (Center for Peace and Conflict Studies (CPCS), 2014)
The history of the All Burma Students Democratic Front (ASBDF) is presented in the form of interviews with and photographs of 36 of its members. It also includes a chronology of the movement.